Topical hesperidin prevents glucocorticoid‐induced abnormalities in epidermal barrier function in murine skin. Issue 9 (31st July 2014) - Man, George; Mauro, Theodora M.; Kim, Peggy L.; Hupe, Melanie; Zhai, Yongjiao; Sun, Richard; Crumrine, Debbie; Cheung, Carolyn; Nuno‐Gonzalez, Almudena; Elias, Peter M.; Man, Mao‐Qiang
Abstract Systemic and topical glucocorticoids (GC) can cause significant adverse effects not only on the dermis, but also on epidermal structure and function. In epidermis, a striking GC‐induced alteration in permeability barrier function occurs that can be attributed to an inhibition of epidermal mitogenesis, differentiation and lipid production. As prior studies in normal hairless mice demonstrated that topical applications of a flavonoid ingredient found in citrus, hesperidin, improve epidermal barrier function by stimulating epidermal proliferation and differentiation, we assessed here whether its topical applications could prevent GC‐induced changes in epidermal function in murine skin and the basis for such effects. When hairless mice were co‐treated topically with GC and 2% hesperidin twice‐daily for 9 days, hesperidin co‐applications prevented the expected GC‐induced impairments of epidermal permeability barrier homoeostasis and stratum corneum (SC) acidification. These preventive effects could be attributed to a significant increase in filaggrin expression, enhanced epidermal β‐glucocerebrosidase activity and accelerated lamellar bilayer maturation, the last two likely attributable to a hesperidin‐induced reduction in stratum corneum pH. Furthermore, co‐applications of hesperidin with GC largely prevented the expected GC‐induced inhibition of epidermal proliferation. Finally, topical hesperidin increased epidermal glutathione reductase mRNA expression, which could counteract multiple functional negative effects of GC on epidermis. Together, these results show that topical hesperidin prevents GC‐induced epidermal side effects by divergent mechanisms.